Estimating the Human Resource Costs of Developing and Implementing Shared Medical Appointments in Primary Care. Issue 1 (January 2016) - Stults, Cheryl D.; McClellan, Sean; Panattoni, Laura; Mazza, Mary Carol; Tai-Seale, Ming
Abstract : We used activity-based costing to estimate the human resource costs for developing and implementing a program to support shared medical appointments (SMAs) and an additional SMA on cancer survivorship. In-depth, key informant interviews were conducted to determine completed tasks, personnel involved, and time to complete tasks. Introducing new providers or a new type of SMA may require relatively modest incremental organizational resources and provider time (<8% of time and about 15% of the finances required to start the initial SMA). Time and cost could possibly be further decreased by leveraging relevant materials from existing SMAs.